Effect of phytochemicals in phoenix Dactylifera L. On human body using LC-QTOF-MS - Elma S.N.; Badarusham K.; Salvamani S.; Hassan M.S.; Dzulfadli Rosli (Indian Journal of Public Health Research and Development, 2024)
Indexed by Scopus